PENGARUH PEER EDUCATION TERHADAP PENGETAHUAN DAN SIKAP MENGENAI PREMENSTRUAL SYNDROM PADA SISWI SMP - Supliyani, Elin; Yanti, Risna Dewi (Jurnal Ilmiah Bidan (JIB), 2022)
One of the trouble that related to menstrual is Premenstrual Syndrfome. Various of information sources about Premenstrual Syndrome that can obtained by the family or by the surroundings and would be better if it obtain by friends or by the same age group where they could more open and more understand to sharing especially in the case of the positive things. Therefore, the effort is needed to provided assistance to the youth to provide knowledge and form positive attitudes about premenstruall syndrome. The effort that can be done is to form a peer group (Peer Group). The purpose of this study was to determine the influence of Peer Education on knowledge and attitude regarding Premenstrual Syndrome in female students of Junior High School in Bogor City with Pre-experimental design , one group pre-test post-test, the sampling technique using Cluster Sampling at Junior High School students 6 grade VII a number of 42 people. Bivariate analysis test Wilkoxon to determine the effect of Peer Education to increase knowledge about Premenstrual Syndrom, while the t-dependent to determine the effect of Peer Education on attitudes regarding Premenstrual Syndrome. The results obtained the increase of knowledge which is significant with p value 0.000 (p<0.005). Similarly, there is an increase in the attitude of a significant with an average of 51.69 be 56.04, p value 0.000 (p<0.005). Peer Education effect on knowledge and attitude regarding Premenstrual Syndrome in female students of JuniorHigh School, therefore adviced to form peer group education in schools and always conduct health education on reproductive health of adolescents, especially about Premenstrual Syndrom. Keywords : Peer Education, knowledge, attitude,